2013
DOI: 10.1080/03004279.2013.804853
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of burnout syndrome of Greek child care workers and kindergarten teachers

Abstract: The present study, employing the Maslach Burnout Inventory -Educators Survey, aims to compare and explore possible differences to the levels of burnout reported by the two main professional groups working in the early childhood education and care sector in Greece, that is kindergarten teachers and childcare workers. The correlation between the levels of burnout reported and participants' demographic data were also examined. Research data revealed that kindergarten teachers experience slightly more feelings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
0
16
0
5
Order By: Relevance
“…Mental load consists of 10 closed items, including different characteristics of work (Time pressure, Low satisfaction, Great responsibility, Dull work, Problems and conflicts, Monotony, Nervousness, Oversaturation, Fatigue, Long-lasting load). A statistical evaluation of the results employs the calculation of the medians for items found to express the measure of agreement/disagreement on the 5-grade scale (1, 2, 3, 4, 5; “1 – strongly disagree”; “2 – mildly disagree”; “3 – neutral”; “4 – mildly agree”; “5 – strongly agree”). Results can be analysed based on an individual or group level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental load consists of 10 closed items, including different characteristics of work (Time pressure, Low satisfaction, Great responsibility, Dull work, Problems and conflicts, Monotony, Nervousness, Oversaturation, Fatigue, Long-lasting load). A statistical evaluation of the results employs the calculation of the medians for items found to express the measure of agreement/disagreement on the 5-grade scale (1, 2, 3, 4, 5; “1 – strongly disagree”; “2 – mildly disagree”; “3 – neutral”; “4 – mildly agree”; “5 – strongly agree”). Results can be analysed based on an individual or group level.…”
Section: Methodsmentioning
confidence: 99%
“…life-changing events, daily hassles) and macro level (occur at the level of social system above the individual). Therefore, exhaustion and overload in teachers predict a higher risk of burnout (3).…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that the duration of professional experience of preschool teachers causes emotional exhaustion in the teachers and they become increasingly insensitive to the teaching process. Therefore, it would not be wrong to claim that the duration of professional experience negatively affect preschool teachers' self-efficacy belief (Rentzou, 2015). However, Kotaman (2010) found that the duration of professional experience of preschool teachers also has a negative impact on classroom management, teaching strategies, student engagement areas, and this was directly related to teacher self-efficacy belief.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, demands are largely constant because although children are “forever young” (i.e., between birth and 3 years old), preschool teachers are aging. Preschool teachers are often professionally satisfied because they are a significant part of the growth of very young children [ 28 , 29 ], nevertheless, several studies demonstrate that working with young children requires responsibility and demands total availability of energy, attention, vigilance, sensitivity, and empathy [ 30 , 31 , 32 , 33 ], and therefore high stress levels and burnout may occur [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%